2005
DOI: 10.1080/09273940590909121
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE Causes of Uveitis in a Referral Hospital in Ankara, Turkey

Abstract: The etiology of uveitis and its associated systemic findings may vary depending on the geographic distribution of patients and local factors. These results represent those of patients with uveitis referred to hospitals in central Anatolia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
26
2
17

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 16 publications
13
26
2
17
Order By: Relevance
“…Consistently, the disease was the leading cause of posterior uveitis (46.1%) and panuveitis (61.0%), and a less common cause of anterior uveitis (9.7%) in our study. Patients presenting with vitritis only, without any accompanying anterior or posterior segment involvement and angiographic leakage, (7)(8)(9). Similar to our study, Kazokoglu et al (10) found BD to be the most frequently associated systemic disease in both posterior uveitis and panuveitis.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Consistently, the disease was the leading cause of posterior uveitis (46.1%) and panuveitis (61.0%), and a less common cause of anterior uveitis (9.7%) in our study. Patients presenting with vitritis only, without any accompanying anterior or posterior segment involvement and angiographic leakage, (7)(8)(9). Similar to our study, Kazokoglu et al (10) found BD to be the most frequently associated systemic disease in both posterior uveitis and panuveitis.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our study, Kazokoglu et al (10) found BD to be the most frequently associated systemic disease in both posterior uveitis and panuveitis. On the other hand, toxoplasmosis, observed in 7.2% of our patients, was the leading cause of posterior segment inflammation in most of the epidemiological studies (3,(7)(8)(9)12). It was the second most common cause of posterior uveitis, with a rate of 27%, and the leading cause of infectious uveitis in our series.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations